Table of Content - - (Journal of Risk and Crisis Management, 2024)
Table of Content: 1. Risks of Electronic Payment Services and Their Relationship to Cybercrimes: An Applied Study on the Payment Services Sector in the Kingdom of Saudi Arabia (July to August 2024) Ms. Nada Mansour Bin Dawood, Dr. Al-Faisal Abdul-Hamid Muhammad, Dr. Fayez Ali Jarad 2. The Role of Graphic Design in Risk and Crisis Management Dr. Mohamed Abdelaziz Mohamed 3. The role of administrative leadership in crisis management in government hospitals in Saudi Arabia during the (Covid -19) Mr. Hathloul Saleh Alshammari 4. The effect of strategic planning in improving the efficiency of crisis management in Jordanian industrial companies Mr. Salem Mohammed Al-Hababi